Real‐World longitudinal practice patterns in the use of PD‐1 and PD‐L1 inhibitors as First‐Line therapy in patients with Non‐Small cell lung cancer in the United States. (2nd May 2022) - Veluswamy, Rajwanth; Hirsch, Fred R.; Taioli, Emanuela; Wisnivesky, Juan; Strauss, Ross; Harrough, Douglas; Tang, Boxiong; Barnes, Gisoo
Abstract: Background: Immune checkpoint inhibitors targeting the programmed cell death protein‐1 (PD‐1) and programmed death ligand‐1 (PD‐L1) axis (collectively referred to as PD[L]1i) have demonstrated clinical benefits in non‐small cell lung cancer (NSCLC) patients. The purpose of this United States‐based real‐world study is to examine changes in the landscape of first‐line therapies for NSCLC since the introduction of PD(L)1i. Methods: Patients with NSCLC initiating first‐line treatment between May 1, 2017, and October 31, 2020, were identified in the IBM MarketScan® database. Patients were assigned groups based on first‐line therapy: PD(L)1i monotherapy, chemotherapy alone, PD(L)1i with chemotherapy, or targeted therapy for patients with actionable driver mutations. Results: A total of 5431 patients with NSCLC starting first‐line treatment were identified: chemotherapy alone 2568 (47%), PD(L)1i with chemotherapy 1364 (25%), PD(L)1i monotherapy 790 (15%), and targeted therapy 709 (13%). The use of PD(L)1i monotherapy and targeted therapy remained consistent, while the percentage of patients receiving PD(L)1i with chemotherapy more than doubled. Over a third of patients in 2019 and 2020 received chemotherapy alone. Patients aged ≥65 years (odds ratio [OR]: 0.80; 95% confidence interval [CI]: 0.68–0.95), females (OR: 0.86; 95% CI: 0.74–0.98), and those with respiratory (OR: 0.82; 95% CI: 0.71–0.94) or kidney (OR: 0.56; 95% CI: 0.40–0.77) disease were less likely to have received PD(L)1i with chemotherapy than patients that received chemotherapy alone. Conclusions: Since the approval of PD(L)1i for NSCLC, their use has significantly increased for first‐line treatment, especially when used in combination with chemotherapy. A significant proportion of patients received chemotherapy alone. Abstract : Since the approval of PD(L)1i for NSCLC, their use has significantly increased for first‐line treatment, especially when used in combination with chemotherapy. A significant proportion of patients received chemotherapy alone.